Stable Diffusion of Innovation: Reimagining the Controversial Adoption of Generative Artificial Intelligence in the Creative Industries - Harvey, Maxime (Imaginations)

(untitled) (York University, 2026)
This article theorizes the controversial adoption of generative artificial intelligence (Gen AI) in the creative industries by articulating a sociology of uses attentive to technological appropriation and controversy analysis. Drawing from ethnographic research in a film cooperative, it introduces the concepts of actions of dissidence, situated dissonance, and critical distance to analyze the uneven negotiation of Gen AI integration. Far from being marginal disruptions, controversies are framed as constitutive of innovation processes, shaping both sociotechnical imaginaries and governance. The article argues that Gen AI’s diffusion must be understood through its overflows, which reveal contested subjectivities, aesthetic values, and political economies of creativity.